Buyer resistance for cartel versus merger - Vikram Kumar; Robert C. Marshall; Leslie M. Marx; Lily Samkharadze (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
Procurement practices are affected by uncertainty regarding suppliers' costs, the nature of competition among suppliers, and uncertainty regarding possible collusion among suppliers. Buyers dissatisfied with bids of incumbent suppliers can cancel their procurements and resolicit bids after qualifying additional suppliers. Recent cartel cases show that cartels devote considerable attention to avoiding such resistance from buyers. We show that in a procurement setting with the potential for buyer resistance, the payoff to firms from forming a cartel exceeds that from merging. Thus, firms considering a merger may have an incentive to collude instead. We discuss implications for antitrust and merger policy.
Keywords: 330